Atomic decomposition of conceptual DFT descriptors: application to proton transfer reactions. Issue 27 (21st July 2015) - Inostroza-Rivera, Ricardo; Yahia-Ouahmed, Meziane; Tognetti, Vincent; Joubert, Laurent; Herrera, Bárbara; Toro-Labbé, Alejandro
<x xml:space="preserve">Abstract</x> We present an atomic decomposition of the molecular energy, reaction force and reaction flux, which is based on Bader's atoms-in-molecules theory.